Peran Interaksi Memori, Pikiran, dan Bahasa dalam Proses Retrieval Kata pada Mahasiswa Penghafal Al-Qur’an - Antono, Mixghan Norman; Halimah, Eti Nur (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study aims to analyze the interaction between memory, thought, and language in the process of word retrieval among Qur’an memorizing students at the dormitory of Universitas Trunojoyo Madura (UTM). The approach used is psycholinguistic with a descriptive qualitative method. The research focuses on the mechanisms of long-term memory formation, cognitive strategies to retain memorization, and the role of language in the repetition and interpretation of Qur’anic verses. Data collection techniques include in-depth interviews and participant observation. The results show that students actively employ repeated reading strategies (muroja’ah), spatial understanding of verse placement in the mushaf, and tasmi’ as forms of active retrieval from long-term memory. These three strategies demonstrate a strong interrelation between cognitive processing, memory function, and language ability. The memorization process of the Qur’an among these students proves to be a complex psycholinguistic activity involving the simultaneous integration of cognitive and linguistic systems. These findings contribute to the reinforcement of psycholinguistic theory in the context of memorization-based education.